2011
DOI: 10.1007/s11270-011-0948-9
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Ni Nanostructures and C/Fe–Ni Composites as Adsorbents for the Removal of a Textile Dye from Aqueous Solution

Abstract: Novel adsorption materials-Fe-Ni nanostructures and C/Fe-Ni composites-with the carbonaceous material coming from sewage sludge, have been developed and evaluated to remove indigo carmine from aqueous solution. The adsorbents were characterized by transmission and scanning electron microscopy, X-ray powder diffraction, IR spectroscopy and BrunauerEmmett-Teller analysis. Sorption kinetics and isotherms were determined and the adsorption behaviours analysed. All adsorbents here studied have exhibited good effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…3b). These results are consistent with those reported in works forming similar nanocomposites using different support materials [3,18]. These relatively small mean sizes of the thus obtained nanoparticles can be associated to the fast way of adding to the mixture solution of the reducing agent (NaBH 4 ), which causes the rapid reduction rate of both metal ions to form nanoparticles fixed on TUF mineral.…”
Section: Tuf/fe-cu Nanocomposite Characterizationsupporting
confidence: 92%
See 3 more Smart Citations
“…3b). These results are consistent with those reported in works forming similar nanocomposites using different support materials [3,18]. These relatively small mean sizes of the thus obtained nanoparticles can be associated to the fast way of adding to the mixture solution of the reducing agent (NaBH 4 ), which causes the rapid reduction rate of both metal ions to form nanoparticles fixed on TUF mineral.…”
Section: Tuf/fe-cu Nanocomposite Characterizationsupporting
confidence: 92%
“…Therefore, the presence of nanostructures favored the removal process of MG dye. The use of Fe-Cu nanostructures supported on natural material or waste material has been reported for removal of azo dye [3]. However triphenylmethane dyes (MG) have not been studied that much with nanostructures adsorbents.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of bimetallic nanoparticles include high surface area and density of reactive surface sites; catalytic effects, which are effective in hydrodehalogenation reactions (10). Previously, it was observed that the combination of porous materials and metal nanoparticles is one of the interesting areas of interdisciplinary research in water treatments (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%